Zaida of al-Andalus between History and Narrative in Spanish and Arabic Sources (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This study discusses the figure of Zaida of al-Andalus and her role in Castilian politics during the reign of Alfonso VI, with a comparison between Spanish and Arabic accounts. The text highlights the conflicts that arose in Castile before Alfonso came to power, involving his struggles with his brothers Sancho and García, along with the accompanying alliances and military confrontations. The research focuses on Alfonso VI’s marriage to Zaida of al-Andalus, a politically significant event that reflects the complex relations between Muslims and Spaniards in al-Andalus. It emphasizes her role in strengthening Alfonso’s authority after his conquest of Toledo. The study also examines the impact of Muslim–Spanish relations on local politics, seeking to reassess the role of Andalusi women in royal politics and to provide a critical understanding of the social and political mechanisms that shaped the alliances and tensions between the Muslim Taifa kings and the Castilians. Special attention is given to the symbolic and strategic dimensions of Zaida’s marriage and its influence on the kingdom’s stability. The findings suggest that Zaida’s marriage was not merely a personal event, but rather a strategic move that contributed to the stability of the kingdom and the balance of power in the 11th century CE / 5th century AH.
Keywords: Zaida of al-Andalus – Alfonso VI – Castile- Spanish Sources- Arabic Sources